MISUSE OF DIGITAL TECHNOLOGY TO THE USE OF TELECOMMUNICATION INDUSTRY TECHNOLOGY DEVICES USED BY CHILDREN - Apdillah, Dicky; Isnaini, Nur; Lubis, Lili Khairani Azhari; Azura, Putri; Siagian, Zairul Abdi (JOURNAL OF HUMANITIES, SOCIAL SCIENCES AND BUSINESS, 2022)
This study will analyze the misuse of technology in the telecommunications industry by examining the technology gadgets used by children, where many youngsters are now too lazy to participate in activities, too lazy to learn, and too reliant on cellphones. There are several instances of children abusing digital tools and devices. Yet, how do youngsters in Indonesia actually utilize the internet? This research is conducted in a library, which is a way of conducting research that involves reading books or periodicals and other data sources in a library. Additionally, this study employs case study and descriptive methodologies. The data and discussion indicate that internet abuse by children fosters a closer connection between children and the internet, particularly those under the age of 12, despite the negative consequence of addiction, which results in children interacting less with other family members and peers. As for other reasons, the internet is frequently seen negatively due to its content, which includes pornography, violence, and cyberbullying. On the other hand, the internet is believed to have a beneficial effect because it may be utilized by youngsters as a tool for learning. As a response, parents must supervise their children's use to avoid any negative consequences. Several prior research have demonstrated that young internet users were exposed to the internet at an early age.